The Disproportionality Analysis of Sainte-Laguë Method Using Gallagher Index in Banggai Regency Legislative Election 2024 : Analisis Ketidakseimbangan Metode Sainte-Laguë Menggunakan Indeks Gallagher dalam Pemilihan Legislatif Kabupaten Banggai Tahun 2024 - andi hartati; Rahmad; Risman Sarifudin (Jurnal Media Hukum, 2026)
This study aims to measure and analyze the level of disproporsionality between the votes obtained by political parties and the number of seats they receive in the 2024 legislative election ini Banggai Regency. It also seeks to assess the effectiveness of the Sainte-Lague method ini achieving proportional representation and identify factors contributing to the level of disproporsionality found in the legislative election in Bangggai Regency. This research uses a quantitative approach to analyze the election results data from the 2024 legislative election in Banggai Regency. The quantitative analysis will be conducted using the Least Squares Index (LSq) or Gallagher Index to determine the level of disproporsionality between the percentage of votes obtained by political parties and the percentage of seats they receive in the legislative council. The findings in this study show the the Gallagher Index at the electoral district level show significant disproporsionality. However, whwn calculated for the overall seats in the Regional House of Representatives (DPRD), this index is relatively small. In the electoral district of Banggai Regency, the Gallagher Index results indicate an average above 8 or within the range of 5-10. This suggest that the LSq/Gallagher Index interpretation of the electoral system in Banggai Regency demonstrates moderate disproporsionality. There is a significant diffrence between the percentage of votes and seats, some parties receive more or fewer seats compared to the percentage of votes the obtain, which can lead to dissatisfaction among voters.